2015
DOI: 10.1186/s12864-015-1825-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptomic analysis of the plant-beneficial rhizobacterium Bacillus amyloliquefaciens SQR9 during enhanced biofilm formation regulated by maize root exudates

Abstract: BackgroundBacillus amyloliquefaciens SQR9 is a plant growth-promoting rhizobacteria (PGPR) with outstanding abilities to enhance plant growth and to control soil-borne diseases. Root exudates is known to play important roles in plant-microbe interactions. To explore the rhizosphere interactions and plant-beneficial characteristics of SQR9, the complete genome sequence as well as the transcriptome in response to maize root exudates under biofilm-forming conditions were elucidated.ResultsMaize root exudates stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 97 publications
9
113
0
3
Order By: Relevance
“…Although there were some differences in the fold-changes for several differentially expressed genes (DEGs) as determined by real-time qPCR and RNA-Seq, the general trends were consistent, supporting the credibility of the RNA-Seq data (Supplementary Table S2). These differences likely result from the use of different methods, a phenomenon that was also observed in previous studies3132.…”
Section: Resultssupporting
confidence: 56%
“…Although there were some differences in the fold-changes for several differentially expressed genes (DEGs) as determined by real-time qPCR and RNA-Seq, the general trends were consistent, supporting the credibility of the RNA-Seq data (Supplementary Table S2). These differences likely result from the use of different methods, a phenomenon that was also observed in previous studies3132.…”
Section: Resultssupporting
confidence: 56%
“…Here cucumber seedlings with fully developed cotyledons (7 days after transplantation) and not at the later six‐leaves stage (∼45 days after transplantation) such as in the study by Liu et al . () were used in order to follow the initial phase of colonization, which is also relevant for the use of PGPR in agriculture (Cao et al, ; Zhang et al, ). Data revealed a significant decrease by approximately two orders of magnitude in the population of root attached bacteria for the mcp free mutant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we have used Bacillus velezensis SQR9 (formerly known as B. amyloliquefaciens ) as a model, which is a well‐studied and commercially widely used PGPR strain (Cao et al, ; Shao et al, ). This strain is chemotactically attracted to cucumber root exudates (Weng et al, ; Zhang et al, ). We have recently determined the chemical composition of cucumber root exudates and demonstrated that 39 compounds (mainly include amino acids, organic acids and sugars) caused chemoattraction whereas five compounds were found to repel the strain (Feng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the transcriptome analysis of B. amyloliquefaciens SQR9 was reported (a member of the BA-PA that also isolated by our laboratory) incubated with maize root exudates [which partially mimicked the presence of a rhizosphere (Zhang et al, 2015)]. Thirteen genes that belong to PA-specific core genome and were gained through HGT at the divergence event between PA and nPA (BA-PA branch), were observed to be induced by root exudates (Tables S3, S8, S10), including mtlA (GP102111, mannitol transporter) and glnQ/M (GP102791/GP102793, glutamine transporters) involved in transport of important compounds in root exudates (Badri and Vivanco, 2009).…”
Section: Discussionmentioning
confidence: 98%